ANALYSIS OF GRAMMATICAL ERRORS IN STUDENT’S WRITING DESCRIPTIVE TEXT ON 8th GRADE JUNIOR HIGH SCHOOL - Nadziyah Shofiroh (ETNOLINGUAL, 2021)
AbstractThis research was to find out the kinds of grammatical errors made by the students and find out the most common error made by the student. Error analysis is needed for a teacher to increase student’s ability in writing especially in grammatical use. These researchers chose 3 backgrounds of text descriptive from students as the sample. The researcher identified the types of each descriptive text writing error made by students in 8th grade in junior high school based on Surface Strategy Taxonomy by Dulay’s theory. Some findings of this research will be written for each error type: omission, addition, misformation, and misorder. Based on the research analysis, 13 total errors are found. the most common grammatical errors made by students in writing descriptive texts were errors in Ommission Error (61,5%). After that, there is Addition Error with 1 error (7.6 %), Misformation with 4 errors (30,7 %), Misorder with 0 grammatical error each (0 %).